2013
DOI: 10.5581/1516-8484.20130093
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic aspects and quality of life of patients with sickle cell anemia

Abstract: BackgroundSickle cell anemia is a chronic inherited disease, widespread in the Brazilian population due to the high degree of miscegenation in the country. Despite the high prevalence, there are few studies describing the characteristics of patients and the impact of the disease on quality of life. ObjectiveTo describe the sociodemographic profile and the impact of the disease on the quality of life of sickle cell anemia patients. MethodsOver 18-year-old patients with sickle cell anemia who attended meetings h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 19 publications
3
28
0
7
Order By: Relevance
“…In managing serious and unpredictable complications, patients with SCD suffer numerous psychosocial problems such as reduced self-esteem, feelings of frustration (7), depression (7)(8)(9), anxiety and stress (8), and disruption of interpersonal relationships (10); these often lead to fatigue (11)(12)(13)(14) and poor quality of life (13,(15)(16)(17) in these patients. Bakri et al (10) showed that depression, anxiety and stress are prevalent in SC patients compared with healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In managing serious and unpredictable complications, patients with SCD suffer numerous psychosocial problems such as reduced self-esteem, feelings of frustration (7), depression (7)(8)(9), anxiety and stress (8), and disruption of interpersonal relationships (10); these often lead to fatigue (11)(12)(13)(14) and poor quality of life (13,(15)(16)(17) in these patients. Bakri et al (10) showed that depression, anxiety and stress are prevalent in SC patients compared with healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…4 The disease also influences these individuals' work capacity: they generally have low income levels and little access to healthcare services, which in turn has a significant impact on quality of life. 5 Functional status and quality of life may be worse among adult patients with sickle cell disease due to the presence of comorbitities, 2 taking into account that psychiatric patients suffer greater harm in terms of quality of life than do patients with no psychiatric comorbidities. 6 In Brazil, it has become a public health issue because it leads to major socioeconomic problems due to the diminished job opportunities that these patients face in the labor market.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with SCD have families, go to school and work, have friends, and function in society. Many studies have also illustrated some of the stressors and physical challenges associated with SCD in adults, children, and families (Dos Santos & Gomes, 2013;Hildenbrand, Barakat, Alderfer, & Marsac, 2013). Complications associated with SCD are rather common and increase in incidence with aging (Blinder et al, 2013).…”
Section: Discussionmentioning
confidence: 98%